Electrical detection of ppb region NO2 using Mg-porphyrin-modified graphene field-effect transistors. Issue 20 (17th August 2021) - Ikuta, Takashi; Tamaki, Takashi; Masai, Hiroshi; Nakanishi, Ryudai; Endo, Kitaro; Terao, Jun; Maehashi, Kenzo
Abstract : The Mg-porphyrin-modified graphene FETs showed NO2 detection at a low concentration of ppb order at room temperature and are highly selective toward NO2 . Abstract : The trace detection of NO2 through small sensors is essential for air quality measurement and the health field; however, small sensors based on electrical devices cannot detect NO2 with the desired selectivity and quantitativity in the parts per billion (ppb) concentration region. In this study, we fabricated metalloporphyrin-modified graphene field-effect transistors (FETs). Mg-, Ni-, Cu-, and Co-porphyrins were deposited on the graphene FETs, and the transfer characteristics were measured. With the introduction of NO2 in the ppb concentration region, the FETs of pristine graphene and Ni-, Cu-, and Co-porphyrin-modified graphene showed an insufficient response, whereas the Mg-porphyrin-modified graphene exhibited large voltage shifts in the transport characteristics. This indicates that Mg-porphyrin acts as an adsorption site for NO2 molecules. An analysis of the Dirac-point voltage shifts with the introduction of NO2 indicates that the shifts were well-fitted with the Langmuir adsorption isotherm model, and the limit of detection for NO2 was found to be 0.3 ppb in N2 . The relationship between the mobility and the Dirac-point voltage shift with the NO2 concentration shows that the complex of NO2 and Mg-porphyrin behaves as a point-like charge impurity. Moreover, the Mg-porphyrin-modified graphene FETs show less response to other gases (O2, H2, acetic acid, trimethylamine, methanol, and hexane), thus indicating high sensitivity for NO2 detection. Furthermore, we successfully demonstrated the quantitative detection of NO2 in air, which is near the environmental standards. In conclusion, the results of the Mg-porphyrin-modified graphene FETs enable a rapid, easy, and selective detectability.